2018
DOI: 10.1136/esmoopen-2018-000353
|View full text |Cite
|
Sign up to set email alerts
|

Optimising the use of cetuximab in the continuum of care for patients with metastatic colorectal cancer

Abstract: The anti-epidermal growth factor receptor (EGFR) monoclonal antibody cetuximab in combination with chemotherapy is a standard of care in the first-line treatment of RAS wild-type (wt) metastatic colorectal cancer (mCRC) and has demonstrated efficacy in later lines. Progressive disease (PD) occurs when tumours develop resistance to a therapy, although controversy remains about whether PD on a combination of chemotherapy and targeted agents implies resistance to both components. Here, we propose that some patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 106 publications
2
40
0
Order By: Relevance
“…Therefore, ctDNA detection appeared to be a useful method for the molecular genotyping and sensitive for monitoring mutational status, which potentially helps to develop treatment strategy targeting actionable variations. Our observations were supported by several previous reports focusing on the monitoring capability of NGS-based liquid biopsy in late-stage CRC therapy (4,(19)(20)(21)(22)(23)(24). However, the regimes used in these studies varied according to different situation.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Therefore, ctDNA detection appeared to be a useful method for the molecular genotyping and sensitive for monitoring mutational status, which potentially helps to develop treatment strategy targeting actionable variations. Our observations were supported by several previous reports focusing on the monitoring capability of NGS-based liquid biopsy in late-stage CRC therapy (4,(19)(20)(21)(22)(23)(24). However, the regimes used in these studies varied according to different situation.…”
Section: Discussionsupporting
confidence: 87%
“…However, the regimes used in these studies varied according to different situation. Some studies focused on the monitoring of cetuximab-based therapy for RAS wild type patients (19)(20)(21), while others emphasize the monitoring of multiple targets, including EGFR, HER2, SMAD4, and NF1 (4, 21-23). Interestingly, one study investigated the ability of both mutation and methylation markers in monitoring (24).…”
Section: Discussionmentioning
confidence: 99%
“…These therapeutic concepts are well approved in large randomized trials in the first line as well second line settings [11,28]. As refractory patients will be seen more frequently in sequential treatment of mCRC re-challenge concepts have been investigated with promising results [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that 21% of patients responded to irinotecan plus cetuximab in the third-line setting, suggesting that the sensitivity to the anti-EGFR antibody was restored over the period of subsequent therapy. The mechanism underlying this loss of resistance is unknown, but the second-line chemotherapy in the absence of cetuximab might play a key role [66]. To date, most anti-HER2 agents, which failed to show clinical benefit, have been examined in the second-line setting, and little is known about their efficacy in the third-or later-line setting.…”
Section: Advantages Of Trastuzumab Deruxtecanmentioning
confidence: 99%